2018
DOI: 10.1177/1470593118772207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating festival attributes adopting S-D logic: The mediating role of visitor experience and visitor satisfaction

Abstract: To symbolize the importance of contextual factors of provision in the contemporary service era, in festival research, the term festivalscape has been proposed. Despite the large number of works investigating the construct, extant research does not adequately assess the systemic and interactive nature of festivals, which can be viewed as a set of interconnected elements. To bridge this gap, this article evaluates four festival attributes (atmosphere, service quality, people interaction and collateral services) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Past research has found that consumer attitudes are one of the most critical antecedents in predicting purchase intentions [11,12,18,52,58]. Moreover, the decision-making process can be influenced by factors such as brand awareness, comparing alternatives, perceived quality, and perceived credibility of the brands and their products [33,48,50,52,54,[59][60][61][62][63]. On the other hand, destination choice is generally understood to be influenced by similar factors as product purchase intentions.…”
Section: Purchase and Visit Intentionsmentioning
confidence: 99%
“…Past research has found that consumer attitudes are one of the most critical antecedents in predicting purchase intentions [11,12,18,52,58]. Moreover, the decision-making process can be influenced by factors such as brand awareness, comparing alternatives, perceived quality, and perceived credibility of the brands and their products [33,48,50,52,54,[59][60][61][62][63]. On the other hand, destination choice is generally understood to be influenced by similar factors as product purchase intentions.…”
Section: Purchase and Visit Intentionsmentioning
confidence: 99%
“…We have been able to address results in the industrial context that are less common in the VcC literature, which has devoted the most attention to the relationship between the company and consumer (B2C) (e.g. [53,54]) or, in second place, between companies (B2B) in the scope of services.…”
Section: Key Findingsmentioning
confidence: 99%
“…and is characterized by a deeply rooted community. The project started in 2012 to meet the seasonal adjustment of tourism flows, ignoring that they were just limited to the summer months ( for seaside tourism) and Christmas time ( for festivals illuminations, Troisi et al, 2017). The project had the challenging remit to build a wiser community of tourism actors, both on the industry side and on the tourist side.…”
Section: Smartour: the Story Of A No Profit Association And A Tourism Appmentioning
confidence: 99%